Formability behavior, microstructural evolution, and mechanical properties of GH4169 and electroformed Ni electron beam welded joint. (October 2022) - Wang, Xiaobing; Wang, Houqin; Qiu, Yu; Yu, Sen; Zhao, Yanhua; Xie, Meirong; Zhang, Binggang
Abstract: The dissimilar joint between GH4169 and electroformed Ni (E-Ni) was prepared by electron beam welding. The incomplete fusion defect of GH4169 and E-Ni joint was solved by the welding method of electron beam offset to the E-Ni side, and the influence of electron beam offset on the joint formation was mainly studied. The microstructure showed that weld metal was primarily composed of γ phase and Laves phase precipitated between dendrites. The influence of the electron beam offset on the mechanical properties of the joint was emphatically studied. When the electron beam offset was increased from 0 mm to 0.6 mm, the hardness of the fusion zone (FZ) decreased from 240 HV to 160 HV, which was caused by the reduction of the γ″ phase and strengthening elements such as Nb, Mo, and Ti in the FZ. The tensile strength of the upper part of the joint was more than 400 MPa, and the elongation after fracture was more than 15%. However, incomplete fusion defects led to a significant decrease in the tensile strength of the lower part welded joint. When the offset was 0.4 mm and 0.6 mm, the strength of the lower part increased to more than 400 MPa. Highlights: The defect-free joint of GH4169/Ni is formed by offset electron beam welding. The effect of offset welding on the microstructure evolution of welds is studied. The relationship among forming, microstructure, and mechanical property of the joints is established. The tensile strength of joints exceeds 400 MPa and the elongation exceeds 15%.